APLIKASI PENGAWET ALAMI LARUTAN KAPUR DAN EKSTRAK TEMPURUNG KELAPA TERHADAP SENSORIS GULA KELAPA CETAK - Gebila Mazaya; Karseno Karseno; Tri Yanto (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Solidified coconut sugar is a product made from the processing of coconut sap. Nutrient content in the sap causes the sap to be easily damaged which must be prevented by antimicrobial agents or natural preservatives. Natural preservatives that are commonly used have limited availability and are difficult to obtain, so we need alternative natural preservatives that can meet the needs of coconut sugar farmers. The purpose of this study was to obtain a natural preservative formula made from a coconut shell that produces the best coconut sugar characteristics. The experimental design used in this study was a Randomized Block Design (RBD) with two factors, namely variations in the type of shell (fresh and dry old shell) and the ratio of lime solution to shell extract (90:10; 80:20 and 70:30). The sensory characteristics of solidified coconut sugar observed include color, texture, aroma, sweetness level and likeness. The results showed the treatment of natural preservative formula with lime solution compared to the extract of fresh old shell with 90:10 rasio produced the best sensory characteristics of solidified coconut sugar with a color value of 2,838 (brown), texture 4,563 (very hard), aroma 3,988 (typical of coconut sugar), level sweetness 4,163 (sweet) and favorite 4 (like).